STUDI ANALISIS KUALITAS AIR DI DAERAH ALIRAN SUNGAI PAKERISAN PROVINSI BALI - asrini, ketut; Sandi Adnyana, I Wayan; Rai, I Nyoman (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 11 No 2 (2017)DO - 10.24843/EJES.2017.v11.i02.p01, 2017)
Pakerisan watershed is used by the people for various purposes to meet the daily needs for water and it is also for irrigation water. The aim of research was to determine the water quality related to human activities and the pollution index. Water sampling was conducted in the nine sample points i.e. upstream of two sample points, in the middle of four sample points, and in the downstream of three sample points. Sampling was done by purposive sampling. Determination of water quality was carried out by comparing the measured data of each parameter of water with the value of quality standards based on the Bali Governor Regulation Number  08 of 2007, while the definition of the status of water quality was done by the pollution index method. The results showed that the activities that affect the water quality physically, chemically and biologically at the upstream to downstream are farming activities, settlements, tourism and trade. In the upstream showed no parameters that exceeded the quality standards, the variables of BOD, COD, phosphate, fecal coli and total coli exceeded the quality standards and in the downstream,  the BOD, fosfat and  fecal coli exceeded the quality standards. The pollution index found in the upstream region good condition, whereas in the middle was classified as heavily polluted until the downstream  was lightly polluted.